Experiences and Reference Solutions to Development Zones in China - Jun Yang; Gang Wu; Qun Wang (Eximia, 2025)
This paper introduces the Silicon Valley of the United States, Singapore’s Science Park, Taiwan’s Hsinchu Science Park and Suzhou Industrial Park, and analyses successful experiences of these development zones in development and construction, then some common characteristics of these parks are summarized. By learning from successful experiences of development zones domestic and abroad, this paper puts forward some inspirations for the construction of China’s development zones.